Histopathological review of breast tumours in children and adolescents in Delta State Nigeria - Francis Nwachokor; Alex Payim Igbe; Gerald Dafe Forae (Wolters Kluwer Medknow Publications, 2013)
Background: Breast swellings in children and adolescents may be overlooked on assumption that they are physiological enlargement. Pathologic swellings including cancers have however been encountered in this age group. This study highlighted the spectrum of tumours in childhood and adolescents. Materials and Methods: This was a 7 year retrospective analysis of all histologically diagnosed breast tumours in people aged 0 - 19 years. Results: There were 134 breast tumour diagnoses occurring in 133 females and 1 male (gynaecomastia). One hundred and nineteen cases (88.8%) were recorded in the 10 - 14 year age group and 15 cases (11.2%) in the 15 - 19 year age group. No case was found in children aged less than 10 years. The most common tumour was fibroadenoma accounting for 75.4% (n = 101) of all tumours followed by tubular adenoma (n = 11; 8.2%) and adenosis (n = 10; 7.4%). No case of malignancy was recorded in this study. Conclusion: Fibroadenoma is the most common breast tumour in children and adolescents in our environment.